High-Performance Carbon Black/Fe3O4/Epoxy Nanodielectrics for Electrostatic Energy Storage and Harvesting Solutions - Sotirios Stavropoulos; Aikaterini Sanida; Georgios Psarras (Energies, 2025)
The present study explores the energy storage and harvesting properties of nanocomposite systems reinforced with carbon black and magnetite nanoparticles (Fe3O4). The systems’ energy storage performance was evaluated under both AC and DC conditions to analyze the impact of temperature, DC charging voltage levels, and varying filler contents on the stored and recovered energy. The experimental findings demonstrated that these systems are capable of efficiently storing and releasing energy on demand via a rapid charge–discharge mechanism. Dynamic mechanical and dielectric analyses revealed significant enhancements in the storage modulus and the energy efficiency of these materials due to the synergistic effects of the nanoparticles and the interactions between them and the polymer matrix. The incorporation of the carbon black and magnetite nanoparticles improves the energy-storage capabilities, supported by augmented interfacial polarization phenomena, which facilitate charge migration and accumulation. These systems exhibit rapid charge and discharge behavior, making them suitable for applications requiring high power density and fast energy storage and recovery cycling. These findings underscore the aptitude of these nanocomposites for high-performance energy-storage solutions, emphasizing their adaptability to applications requiring both high energy density and efficient recovery in tandem with adequate thermomechanical performance.